PEMENTASAN DRAMA DALAM PEMBELAJARAN BAHASA INDONESIA SEBAGAI SARANA MENGENALKAN KEBERAGAMAN INDONESIA - Said Agil; Roihan Ali; Evi Mauliatul H; Fendi Pradana; Mahin Ainun Naim (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT This study was motivated by the importance of Indonesian language learning that not only focuses on mastering language skills but also plays a role in improving students’ understanding of Indonesia’s cultural diversity. However, Indonesian language learning in schools still tends to use conventional methods, resulting in limited student involvement in understanding multicultural values. This study aims to describe the implementation of drama performances in Indonesian language learning and their influence on students’ communication skills and understanding of cultural diversity. This study employed a descriptive qualitative method with data collection techniques consisting of observation, interviews, and documentation. The research subjects were students participating in drama performance activities in Indonesian language learning. The results showed that the implementation of drama performances was conducted through the stages of delivering drama materials with cultural diversity themes, group discussions in preparing drama scripts, and rehearsal and performance activities in front of the class. These activities created active, contextual, and participatory learning because students were directly involved in role-playing and character interpretation. In addition to improving students’ speaking skills, expression, intonation, and self-confidence, drama performances also helped students understand the values of tolerance, empathy, cooperation, and appreciation for Indonesia’s cultural diversity. This study contributes to strengthening multicultural-based Indonesian language learning through the use of drama performances as a contextual learning medium and a strategy for character building. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya pembelajaran Bahasa Indonesia yang tidak hanya berfokus pada penguasaan keterampilan berbahasa, tetapi juga berperan dalam meningkatkan pemahaman peserta didik terhadap keberagaman budaya Indonesia. Namun, pembelajaran Bahasa Indonesia di sekolah masih cenderung menggunakan metode konvensional sehingga keterlibatan siswa dalam memahami nilai multikultural belum optimal. Penelitian ini bertujuan mendeskripsikan implementasi pementasan drama dalam pembelajaran Bahasa Indonesia serta pengaruhnya terhadap keterampilan komunikasi dan pemahaman keberagaman budaya siswa. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Subjek penelitian adalah siswa yang mengikuti kegiatan pementasan drama dalam pembelajaran Bahasa Indonesia. Hasil penelitian menunjukkan bahwa pelaksanaan pementasan drama dilakukan melalui tahap penyampaian materi drama bertema keberagaman budaya, diskusi kelompok dalam penyusunan naskah, serta latihan dan pementasan drama di depan kelas. Kegiatan tersebut mampu menciptakan pembelajaran yang aktif, kontekstual, dan partisipatif karena siswa terlibat langsung dalam bermain peran dan interpretasi tokoh. Selain meningkatkan keterampilan berbicara, ekspresi, intonasi, dan rasa percaya diri siswa, pementasan drama juga membantu siswa memahami nilai toleransi, empati, kerja sama, serta penghargaan terhadap keberagaman budaya Indonesia. Penelitian ini memberikan kontribusi berupa penguatan pembelajaran Bahasa Indonesia berbasis multikultural melalui pemanfaatan pementasan drama sebagai media pembelajaran kontekstual